FROM LABORATORY TO CLINICAL - TREATMENT OF HYPERPIGMENTATION POST-INFLAMMATORY, ANTI-MICROBA AND BODY ODOR IN AXILLARY REGION WITH TISSUE INNOVATION COMPOSITED PIONIN, ALOE VERA, GLUTATHIONE, AND LAVENDER - Tan, Sukmawati Tansil; Firmansyah, Yohanes (Perhimpunan Kesehatan Holistik Indonesia, 2021)
It is generally recognized that hyperpigmentation post-inflammatory and body odor issues can be distressing. This will also have an effect on the overall quality of life. As a result, we require a therapy that may address both post-inflammatory hyperpigmentation and body odor issues. The goal of this study was to see if the invention's combination had any antibacterial properties, as well as if it might lessen or fade the signs of hyperpigmentation post-inflammatory. It is believed that the antibacterial action of the current innovation would minimize patients' body odor. This composition is in accordance with the Regulation of the Head of the Drug and Food Control Agency of the Republic of Indonesia Number 12 of 2019 concerning Contaminants in Cosmetic. The axillary tissue cleansing formulation comprises pionin, aloe vera, glutathion, and lavender, all of which have been shown in the laboratory to prevent bacterial development. Clinically, however, the administration of this intervention was demonstrated to be capable of reducing or fading the symptoms of hyperpigmentation post-inflammatory and relieving body odor with very little adverse effects.